2012
DOI: 10.1111/j.1600-0587.2011.07430.x
|View full text |Cite
|
Sign up to set email alerts
|

Niche conservatism and the differences in species richness at the transition of tropical and subtropical climates in South America

Abstract: Although detected long ago, latitudinal disparity in species richness lacks a consensus regarding its underlying mechanisms. We evaluated whether the main predictions derived from the tropical niche conservatism hypothesis help to explain differences regarding species richness and turnover of species and lineages between forests located in tropical and subtropical climates. If tropical niches are retained, we predict that only a subset of tropical lineages disperses and establishes outside the tropics; tip‐lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 42 publications
5
38
2
Order By: Relevance
“…Few studies have examined geographic variation of phylogenetic relatedness of species at a broad geo- graphic extent, and, to our knowledge, our study is the first to examine phylogenetic relatedness of plant species in regional assemblages along the gradients of MINT across a continental region. Nevertheless, both Kooyman et al (2011) and Giehl & Jarenkow (2012) found that woody species in subtropical and warm temperate samples are more phylogenetically clustered than those in tropical samples, which is consistent with our finding. Giehl & Jarenkow (2012) examined phylogenetic relatedness of trees in local assemblages (c. 1 ha) constrained to only about 10°in latitude in tropical and subtropical regions in South America.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Few studies have examined geographic variation of phylogenetic relatedness of species at a broad geo- graphic extent, and, to our knowledge, our study is the first to examine phylogenetic relatedness of plant species in regional assemblages along the gradients of MINT across a continental region. Nevertheless, both Kooyman et al (2011) and Giehl & Jarenkow (2012) found that woody species in subtropical and warm temperate samples are more phylogenetically clustered than those in tropical samples, which is consistent with our finding. Giehl & Jarenkow (2012) examined phylogenetic relatedness of trees in local assemblages (c. 1 ha) constrained to only about 10°in latitude in tropical and subtropical regions in South America.…”
Section: Discussionsupporting
confidence: 90%
“…tree species are more phylogenetically clustered in areas with lower MINT, provides direct support to a key prediction of the phylogenetic niche conservatism hypothesis. Phylogenetic niche conservatism hypothesis in general and tropical conservatism hypothesis in particular (Wiens & Donoghue, 2004) have been formulated to explain differences in species diversity between tropical and temperate regions but neither Kooyman et al (2011) nor Giehl & Jarenkow (2012) included temperate regions. Kooyman et al (2011) examined phylogenetic relatedness of woody plants in local assemblages (c. 0.1-0.5 ha) in tropical and subtropical regions in eastern Australia but they did not relate measures of phylogenetic relatedness to climatic variables in general and MINT in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Bridge species are remarkably pervasive in marine bivalves and are also known in terrestrial clades (61,62); their evolutionary and biogeographic role deserves investigation. However, caution is needed when inferring process from present day species distributions, as species have almost certainly been repositioned by repeated, extensive reshuffling in response to Pleistocene climate fluctuations in both marine and terrestrial settings (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…Qian et al . () for China, Giehl & Jarenkow () for Brazil, Kooyman et al . () for Australia], but not at a global scale.…”
Section: Introductionmentioning
confidence: 92%